2003
DOI: 10.1046/j.1365-2842.2003.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory laterality – evaluation and influence of food texture

Abstract: The purpose of this study is the objective and quantitative evaluation of masticatory laterality and its daily variability. Various foods with different textures were used to investigate whether food texture influenced masticatory laterality. Ten healthy subjects and seven foods were used. Recordings of chewing movements were repeated three times at intervals of 1 week. Masticatory laterality was assessed with an Asymmetry Index [AI: (number of right side strokes - number of left side strokes)/number of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 8 publications
4
54
0
4
Order By: Relevance
“…3,5,26 In this study, most subjects preferred to chew on the right side, as was found by other authors. 10,11 Peripheral factors such as side differences in occlusal contact area and in bite force showed a positive and significant correlation with masticatory laterality.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…3,5,26 In this study, most subjects preferred to chew on the right side, as was found by other authors. 10,11 Peripheral factors such as side differences in occlusal contact area and in bite force showed a positive and significant correlation with masticatory laterality.…”
Section: Discussionsupporting
confidence: 84%
“…Chewing gum was used in most studies, 2,4,7,9,10,13,14,25 although carrots, 3,16 almonds 18 and other foods have also been used. 11,26,27 It is known that the size, texture and hardness of the bolus affects muscle activity and the chewing cycle. 5,11,15,[26][27][28] Although most studies of masticatory performance use tablets of a silicone impression material, 29,30 no studies have assessed chewing side preference using this standardised test food.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…This threshold was selected in order to obtain three balanced groups and according to other studies. 16,17 Page 9 of 20 A c c e p t e d M a n u s c r i p t 9 Statistical analysis was performed using the spss software package (version 20.0; SPSS, Chicago, IL, USA) and P-values below 0.05 were considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…The side of mandible lateralisation while closing was counted for each chewing cycle using a slow-speed playback mode to calculate masticatory laterality. The asymmetry index (AI) for each free-style mastication of bagged or unbagged silicon, was calculated according to Mizumori et al, 17 as…”
Section: Masticatory Assaysmentioning
confidence: 99%